Engineering Properties of Treated Natural Hemp Fiber-Reinforced Concrete - Zhou, Xiangming; Saini, Harmeet; Kastiukas, Gediminas (Frontiers in Built Environment, 2017)
In recent years the construction industry has seen a significant rise in the use of natural fibres, for producing building materials. Research has shown that treated hemp fibre reinforced concrete (THFRC) can provide a low-cost building material for residential and low rise buildings, whilst achieving sustainable construction and meeting future environmental targets. This study involved enhancing the mechanical properties of hemp fibre reinforced concrete through the Ca(OH)2 solution pre-treatment of fibres. Both untreated (UHFRC) and treated (THFRC) hemp fibre reinforced concrete were tested containing 15mm length fibre, at a volume fraction of 1%. From the mechanical strength tests, it was observed that the 28-day tensile and compressive strength of THFRC was 16.9 and 10% higher, respectively than UHFRC. Based on the critical stress intensity factor (K_IC^s), and critical strain energy release rate (G_IC^s), the fracture toughness of THFRC at 28 days was also found to be 7-13% higher than UHFRC. Additionally, based on the determined brittleness number (Q) and modulus of elasticity, the THFRC was found to be 11% less brittle and 10.8% more ductile. Furthermore, qualitative analysis supported many of the mechanical strength findings through favourable surface roughness observed on treated fibres and resistance to fibre pull-out.